2021
DOI: 10.1088/1755-1315/761/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Macrophomina phaseolina (Tassi) Goid Culture Filtrates is a Lucrative Source for Weed Control

Abstract: The mycoherbicides have been recognized as an effective approach for weed control as being eco-friendly, low cost, and of long-lasting. This research was carried out to evaluate the herbicidal effect of Macrophomina phaseolina, the causal of sesame charcoal rot. The fungal culture was extracted with water and the extract toxicity was evaluated by seed germination, detached leaf, and whole plant bioassays on several weed species of Iraq (Cynanchum actum, Malva parviflora, Sorghum halepense, Lolium rgidum, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The aqueous extract of Macrophomina phaseolina culture filtrate inhibited the seed germination of Convolvulus arvensis, Malva neglecta and Sorghum halepense. Moreover, the in vitro and in vivo studies also revealed that the aqueous extract of Macrophomina phaseolina culture filtrate produced phytotoxic damage to Malva neglecta, Convolvulus arvensis, Poa pratensis and Sorghum halepense (Theer et al 2021).…”
Section: Cell-free Culture Filtrates With Herbicidal Valuesmentioning
confidence: 96%
“…The aqueous extract of Macrophomina phaseolina culture filtrate inhibited the seed germination of Convolvulus arvensis, Malva neglecta and Sorghum halepense. Moreover, the in vitro and in vivo studies also revealed that the aqueous extract of Macrophomina phaseolina culture filtrate produced phytotoxic damage to Malva neglecta, Convolvulus arvensis, Poa pratensis and Sorghum halepense (Theer et al 2021).…”
Section: Cell-free Culture Filtrates With Herbicidal Valuesmentioning
confidence: 96%
“…However, the crop productivity has decreased significantly in recent years due to continue development of plant pathogens, which led to critical fluctuations in crop productivity [3]. Charcoal rot disease, caused by the Macrophomina phaseolina, is described as one of the most important determinants of sunflower crops and results in significant yield losses [4][5]16]. Also, root rot and seedling damping-off disease caused by Rhizoctonia is one of the most common soil-and seed-borne plant pathogenic fungi with a wide family range leading to high yield losses [1,17].…”
Section: Introductionmentioning
confidence: 99%